2019
DOI: 10.1093/jxb/erz562
|View full text |Cite|
|
Sign up to set email alerts
|

Four bottlenecks restrict colonization and invasion by the pathogen Ralstonia solanacearum in resistant tomato

Abstract: Ralstonia solanacearum is a bacterial vascular pathogen causing devastating bacterial wilt. In the field, resistance against this pathogen is quantitative and is available for breeders only in tomato and eggplant. To understand the basis of resistance to R. solanacearum in tomato, we investigated the spatio-temporal dynamics of bacterial colonization using non-invasive live monitoring techniques coupled to grafting of susceptible and resistant varieties. We found four ‘bottlenecks’ that limit the bacterium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 41 publications
4
85
0
Order By: Relevance
“…When viewed from the side, it was clear that the white occlusions were continuous within the tapered xylem vessels. This suggested that the occlusions were a dense gel formed by bacterial biofilms seen in our and others’ previous microscopic analyses of Ralstonia -infected stems (Vasse et al 1995; Caldwell et al 2017; Planas-Marquès et al 2020).…”
Section: Resultssupporting
confidence: 66%
“…When viewed from the side, it was clear that the white occlusions were continuous within the tapered xylem vessels. This suggested that the occlusions were a dense gel formed by bacterial biofilms seen in our and others’ previous microscopic analyses of Ralstonia -infected stems (Vasse et al 1995; Caldwell et al 2017; Planas-Marquès et al 2020).…”
Section: Resultssupporting
confidence: 66%
“…2013 ). Hawaii 7996 resistance to the RSSC is expressed in both root and shoot tissues ( Planas-Marquès et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of Hawaii 7996 to bacterial wilt relies on polygenic traits ( Thoquet et al 1996 ; Carmeille et al. 2006 ) and is expressed in both root and shoot tissues ( Planas-Marquès et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…If a pathogen manages to reach the xylem, this transport system becomes an excellent channel of inoculum dissemination throughout the plant. As a consequence, plants have evolved effective structural defense mechanisms to prevent vessel colonization or movement between vessels once vascular colonization has occurred ( Beckman and Roberts, 1995 ) Timely formation of these physico-chemical vascular barriers early upon pathogen perception can lead to confinement of the vascular pathogen at the infected vessel, avoiding the spread of wilt diseases ( Robb et al , 2007 ; Zaini et al , 2018 ; Planas-Marquès et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%